# math

posted by .

-8a^2+5ab-12a^2-6(2a^2-4ab-10n^2)

• math -

Is the n^2 supposed to be an a^2 ?

If so, you can combine three pairs of terms. Otherwise, two pairs.

Just multiply each term in parentheses by 6 and combine "like" terms.

You may also able to factor, after that.

You should try this yourself instead of looking for a web site (including jiskha) to do it for you.

## Similar Questions

1. ### Math

what are the answers to the following questions?
2. ### Tirginometry

the expression 4ab(square root of)2b-3a(square root of)18b^3+7ab(square root of)6b is equivalent to... (a)2ab(square root of)6b (b)16ab(square root of)2b (c)-5ab+7ab(square root of)6b (d)-5ab(square root of)2b+7ab(square root of)6b …
3. ### math

Simplify the Expressions 1) -4(3x-3) + 9(x+1)= -3x21 2) -9x(5x+4)+10(x+3)= -45x-26 x+3 3) n(1+ 10n)-n(4n-3)= 4n+6n 4) -2n(-8n-10)-6(-10n-3)= 96n - 10 5) 8(-4x-7)+3(9-9x)= 59x - 29 6) 9(3-10n)-3(10n+1)= 30n - 3 7) -4(1-8x)-9(-10x-1)= …
4. ### Math 117B Help

subtract (xy-ab-6)-(xy-5ab-5) How do I do this
5. ### math

perform indicated operations. (5ab)/(a^2-b^2)+(a+b)/(a-b)
6. ### algebra

(3a^4b+4ab^3)+(5ab^3-3a^4b
7. ### algebra

simplify -2a^+6ab^-12a^b/-24ab the b -12a^b the b is to the third power 2a^b/24ab + 6ab^/24ab -12a^b to the third/24ab 12a+4ab +2ab^ 2ab^+4ab +12a
8. ### algebra

simplify 2a^2 + 6ab^2-12a^2b^3 divided by 24ab -2a^2/-24ab + 6ab^2/24ab--12a^2b^3/24ab= -12ab^2 +12a +4b
9. ### Math

My Math Problem is {4/5n + 9/2} = 49/10 8/10 45/10n = 53/10n 53/10 x 49/10 = 490/530 n= 60 am I correct
10. ### Math

What are the like terms in this expression?

More Similar Questions